Personal connections and space: a comparative study of the agency of aristocratic women in mid-Tudor England - Chambers, Emily Jayne (2024)
The mid-Tudor period was one of political and religious instability and uncertainty in England, creating both opportunities and significant dangers for those close to power. This thesis examines the influence of personal connections on the agency of eight royal and noble women between the mid-1530s and late 1550s across the domestic, local and religious, scholarly, elite social, and high political and royal court spaces. These women are Frances Brandon, Duchess of Suffolk; Margaret Douglas, Countess of Lennox; Jane Guildford, Duchess of Northumberland; Mary Howard, Duchess of Richmond; Queen Katherine Parr; Anne Stanhope, Duchess of Somerset; Lady Mary Tudor, later Mary I; and Katherine Willoughby, Duchess of Suffolk. This thesis offers a comparative study of these eight women based on archival research, using a range of written primary source material to challenge the positivity of existing scholarship on networks and connections, and to advance our understanding of female participation in the mid-Tudor court. This thesis argues that, despite potential hostility or failings, networks of personal relationships were valuable resources for these elite women to access power and to navigate the mid-Tudor volatility. These relationships served to connect them to central power across distances, and allowed them to both seize opportunities and mitigate losses. These women usually worked on behalf of their families, demonstrating their strong dynastic identities. This thesis demonstrates that not all relationships were positive, and that a reliance on support networks could limit female agency by limiting the assistance offered to these women, restricting their influence or success, or ensuring their dependency on male relatives. This underscores the confines of patriarchal power on even elite women; their subordination was not wholly overcome by recourse to their personal connections. Nonetheless, such relationships were crucial means of assistance to these women to help them negotiate space and traverse the precarity of the mid-Tudor period.